American government: political change and institutional development - Cal Jillson (Routledge, 2008)
In this introductory American politics text, Cal Jillson provides not only a sense of how politics works today but also how institutions, systems, political participation, and policies have developed over time to produce today's political environment in the United States. This historical context provides the necessary backdrop for students to understand why things work the way they do now. Going one step further, the book identifies critical reforms and how American democracy might work better